BIOFUELS AND ABSOLUTE COUPLING. POTENTIAL AND CHALLENGES FOR A SUSTAINABLE FUTURE - Maricel CAZACU; Liviu MARCUTA; Alina MARCUTA; Camelia HODOSAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Absolute decoupling is an economic and sustainability concept that refers to the complete separation of economic growth from natural resource use and environmental impact. This form of decoupling is observed when an economy sustains its growth while the consumption of resources and greenhouse gas emissions decline, signifying an enhancement in resource efficiency and a reduction in environmental impact. Absolute decoupling is considered essential to achieving sustainable development goals, as it offers a solution to developing economies without exacerbating ecological problems such as climate change, biodiversity loss and soil degradation. In this context, biofuels have a significant role, because their utilization can aid in reducing carbon dioxide emissions, thereby facilitating the decoupling of greenhouse gas emissions from economic growth. However, their positive effects depend on several factors, such as cultivation methods, the types of biomass used and the efficiency of the production process, so that the negative ecological impact of their use does not counteract the benefits offered by reducing CO2 emissions. Another relevant aspect of the relationship between biofuels and absolute decoupling is their potential to encourage innovation in the energy sector. By investing in and developing second- or third-generation bioenergy technologies that use organic waste and residues, biofuels can become more sustainable, this approach contributes to reducing natural resource consumption and minimizing ecosystem impact. The current study undertook a bibliographic analysis focused on the objective of absolute decoupling and the role of biofuels in achieving this goal, and on the other hand from the collection, processing and interpretation of statistical data regarding energy consumption, CO2 emissions, production and the consumption of biofuels. The findings revealed a steady rise in these factors, suggesting a direct correlation between economic expansion and its environmental impact. The growth in biofuel production and consumption illustrates the effort regarding the transition to more sustainable energy sources. However, CO2 emissions continue to have an upward trend, which requires the intensification of efforts to increase the share of renewable energy and reduce the intensity of emissions, so that economic growth is sustainable and with minimal effects on climate change.